2018
DOI: 10.1002/ente.201700486
|View full text |Cite
|
Sign up to set email alerts
|

About the Technological Readiness of the H2 Generation by Hydrolysis of B(−N)−H Compounds

Abstract: At the beginning of the new millennium, hydrolysis of sodium borohydride (NaBH4) was presented as a promising on‐board technology to generate H2 for light‐duty vehicles. Years later, other B(−N)−H compounds (e.g., lithium borohydride (LiBH4) and ammonia borane (NH3BH3)) emerged as attractive alternatives whereas NaBH4 was struggling with several issues jeopardizing its implementation. Actually, efforts in the research and development of H2 generation by hydrolysis of B(−N)−H compounds have been intensive since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 203 publications
(445 reference statements)
0
43
0
Order By: Relevance
“…8,9 While most B-N based compounds such as hydrazine borane (N2H4BH3) or metal borohydrides such as sodium borohydride (NaBH4) and lithium borohydride (LiBH4) suffer from self-hydrolysis in water, AB, being the simplest B-N compound, has a high H2 content (19.5 wt%), low molecular weight (30.9 g mol - 1 ), non-toxic nature, and particularly high stability in both aqueous solutions and air. 10 Therefore, AB has a great potential for practical on-board applications in transportation. The release of H2 from AB can be achieved either from thermolysis or solvolysis; the latter can be further classified into hydrolysis and methanolysis, in which the dehydrogenation reaction occurs in water or methanol, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 While most B-N based compounds such as hydrazine borane (N2H4BH3) or metal borohydrides such as sodium borohydride (NaBH4) and lithium borohydride (LiBH4) suffer from self-hydrolysis in water, AB, being the simplest B-N compound, has a high H2 content (19.5 wt%), low molecular weight (30.9 g mol - 1 ), non-toxic nature, and particularly high stability in both aqueous solutions and air. 10 Therefore, AB has a great potential for practical on-board applications in transportation. The release of H2 from AB can be achieved either from thermolysis or solvolysis; the latter can be further classified into hydrolysis and methanolysis, in which the dehydrogenation reaction occurs in water or methanol, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, the storage capacities of sorbents at ambient conditions are very low. In contrast, with borohydrides and boranes, which are H carriers, hydrogen storage and release may be effective at 20–100 °C, because of stronger binding energies than adsorption . This is what is called chemical H storage.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, with the MOF denoted MOF-5(i.e.,Zn 4 O(BDC) 3 with BDC as 1,4-benzenedicarboxylate), ac ubic 3D structure displaying as pecific surfacea rea of about 3800 m 2 g À1 ,i tw as reported that an adsorptiono f7 .1 wt %H 2 (i.e.,7 1g H2 kg MOF À1 )c ould be achieved at À196 8Ca nd 40 bars H 2 . [11] However,t he storage capacities of sorbents at ambient conditions are very low.I nc ontrast, with borohydrides andb oranes, whicha re Hc arriers, hydrogen storagea nd release may be effective at 20-100 8C, [12] because of stronger binding energiest han adsorption. [9] This is what is called chemical Hs torage.…”
Section: Introductionmentioning
confidence: 99%
“…So far, chemical hydrides are the most promising approaches for hydrogen storage since their high gravimetric capacity. Among the chemical hydrides, NH 3 BH 3 due to its high gravimetric capacity of 196 g H 2 /kg, superior regeneration performance, portable, and easy to store when not in use has become one of the most preferable hydrogen storage medium …”
Section: Introductionmentioning
confidence: 99%
“…Among the chemical hydrides, NH 3 BH 3 due to its high gravimetric capacity of 196 g H 2 /kg, superior regeneration performance, portable, and easy to store when not in use has become one of the most preferable hydrogen storage medium. [7][8][9] Hydrogen can be acquired from AB dehydrogenation by means of thermolysis or hydrolysis or in other organic solvents (eg, alcoholysis). Solid AB and aqueous AB solution reported hydrogen release by temperatures of 500 and 393 K, respectively.…”
Section: Introductionmentioning
confidence: 99%